Checklist for Improving Patient Communication on Bladder Preservation Options: The Patient Advocate Perspective. Issue 10 (October 2022) - Bangs, R.; Quale, D.Z.; Reed, T.
Abstract: Trimodal therapy (TMT) – maximal transurethral resection of bladder tumour followed by chemotherapy and radiation – is an effective treatment for some patients diagnosed with muscle-invasive bladder cancer. Yet eligible patients are not always offered this option or are unclear that this option is (or was) appropriate, desirable and available to them. Communication challenges are a critical barrier to delivering the high-quality care and shared decision-making that bladder cancer patients seek. Leveraging patient and clinician feedback, a checklist was created and is proposed that proactively addresses patients' concerns and questions and ensures that patients are well-informed about TMT. By using the checklist, members of multidisciplinary bladder cancer medical teams can ensure that patients are well-informed about TMT and are confident that TMT has been appropriately and jointly explored as a treatment option. The checklist can reduce communication challenges and frustrations and ensure that, through shared decision-making, patients have chosen their most appropriate treatment. Highlights: Patients are not always offered or are unclear about trimodal therapy (TMT). Communication is a barrier to high-quality care and shared decision-making. Patient and clinician feedback was leveraged in making a TMT clinician checklist. The checklist can ensure that patients are well-informed about TMT.